RECEIVABLES’S CONTROL WITH LOCKING SYSTEM: A CASE STUDY OF PT.PELABUHAN INDONESIA III (PERSERO) BRANCH OF TANJUNG PERAK - Martina, Sheila Fitria (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this research is to assess the effectiveness of locking system for receivables control. The object of this research is the locking system of PT. Pelabuhan Indonesia III (Persero) Branch of Tanjung Perak in 2010-2012. This company provides port services for more than 21,000 service users and its value of account receivables is quite material. This research is a case study with a qualitative descriptive approach. The result using financial ratios which are: accounts receivable turnover ratio, average age of accounts receivable, ratio of arrears, and the ratio of billing confirm the effectiveness of locking system in the control of receivables. This study suggests that the collection of accounts receivable in the implementation still needs some improvement. Keywords: Locking System, Financial Ratio, Receivables, and Receivables’s Control